A Working Model for the Integration of Spirituality in Counseling - Matise, Miles (Journal of spirituality in mental health, 2018)
This article addresses the importance of counselors being open to the spirituality of clients as an orienting worldview. The need for a spiritual strategy is addressed and a spiritual awareness decision tree is presented to aid the counselor to determine whether or not to address spirituality with clients, as well as the spiritual awareness guide (SAG). The SAG can help the counselor meet the client at an appropriate cognitive level, conceptualize the client's issues in a spiritual context, and guide prognosis and treatment for the client experiencing a spiritual crises. Implications for counselors are addressed.